University Academic Writing:State of the Art - Ortiz Casallas, Elsa Maria (Íkala, Revista de Lenguaje y Cultura, 2011)
This paper presents a general analysis of the state of the art studies in international and national context (Colombia) about academic writing university. Its objective is to establish the current state of intellectual field and propose new investigative trails that explain, con-textualize and better understand the problems that students present concerning academic writing university. The documents found, research and thesis-were examined and analyzed using the approaches, methodology and theoretical frameworks found in them. The results of the study indicate that, in general, the research trend in academic writing, including the university, has been more focused on the strategy (De Certeau, 1996) via regulation and discipline of writing practices, which in the identification and own analysis of the tactics and practices of scriptural academic work of students and teachers. Rare are the works that document practices and analyze the social representations to see what happens from the field dominated towards a strategy, and what relationships and discontinuities are established between them.